2007
DOI: 10.1111/j.1537-2995.2007.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of fetal red blood cells in maternal blood by a dual‐color flow cytometric method: evaluation of the Fetal Cell Count kit

Abstract: With this new dual-color flow cytometric method, accurate evaluation of fetomaternal hemorrhage was achieved even in the face of HbF of maternal origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 52 publications
3
38
0
5
Order By: Relevance
“…However, this assay lacks specificity and exhibits a large inter-observer variation resulting in potential overtreatment risks related to plasma-derived products and unnecessary treatment cost (20)(21)(22). In accordance with previous studies, we reported an overestimation of FMH by the KBT (12,15,23). The KBT presents stained maternal F cells that may be counted as fetal RBCs, leading to these false positive results (20,23,24).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…However, this assay lacks specificity and exhibits a large inter-observer variation resulting in potential overtreatment risks related to plasma-derived products and unnecessary treatment cost (20)(21)(22). In accordance with previous studies, we reported an overestimation of FMH by the KBT (12,15,23). The KBT presents stained maternal F cells that may be counted as fetal RBCs, leading to these false positive results (20,23,24).…”
Section: Discussionsupporting
confidence: 68%
“…An accurate quantification of FMH is important and defines the right dose of anti-D therapy. The KBT is an efficient screening test, when performed with correct attention in an experienced center (8,15). However, this assay lacks specificity and exhibits a large inter-observer variation resulting in potential overtreatment risks related to plasma-derived products and unnecessary treatment cost (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concomitant test controls to validate and monitor the quality of flow cytometric procedures were performed using FetalTrol ᮋ test samples (IQ-Products, Groningen, The Netherlands). In concomitant test controls and spiking experiments, we were able to confirm the level of quantification of 0.05% fetal RBC when screening 2=10 6 maternal erythrocytes, as described by Porra et al (2007) w18x.…”
Section: Methodsmentioning
confidence: 56%